Islam dan Gender Perspektif Islam Kontemporer terhadap Kesetaraan Gender - Arni Dwi Yana; Muflihah Salahuddin; Abbas (STKIP Subang, 2026)
Abstract This study examines gender equality in Islam within Indonesia's context as the world's largest Muslim-majority nation in the digital era. Employing literature review and documentation analysis methods, it describes the Quranic theological foundation (Al-Hujurat:13, An-Nahl:97, khalifah Al-Baqarah:30) affirming substantial equality, contemporary Islamic feminism developments by Amina Wadud et al., and digital transformation via TikTok democratizing gender discourse. Key findings reveal significant opportunities such as global sisterhood, digital Islamic feminism, and creative economy for Muslim women, yet facing challenges like digital polarization, cyberbullying, misinformation, and digital divide. The conclusion recommends gender-sensitive integrative Islamic education and progressive reinterpretation to harmonize Pancasila values with Islamic justice, positioning Islam as rahmatan lil alamin in contemporary gender practices.